BOUNDARY VALUE PROBLEM FOR A LOADED HEAT CONDUCTIVITY OPERATOR - Shaldykova, B.A.; Akhmanova, D.M.; Shamatayeva, N.K.; Amangeldiev, M.D. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The steadily growing interest in the study of loaded differential equations is explained by the expanding scope of their applications and the fact that loaded equations constitute a special class of functional differential equations with their own specific tasks. These equations are used in the study of inverse problems of differential equations, which have important applied significance. The paper investigates the solvability problems of homogeneous and nonhomogeneous boundary value problems, as well as spectral issues for loaded differential operators of mathematical physics, when the loaded terms are not a weak perturbation of the differential part of the operator. They require special theoretical research.